Decisional conflict in patients considering diagnostic thyroidectomy with indeterminate fine needle aspirate cytopathology. Issue 1 (December 2016) - Taylor, Benjamin; Hart, Robert; Rigby, Matthew; Trites, Jonathan; Taylor, S.; Hong, Paul
Abstract Background Fine needle aspiration (FNA) cytopathology is the gold standard work-up for thyroid nodules. However, indeterminate lesions are encountered commonly and can lead to difficult treatment decisions. We sought to determine whether patients experienced decisional conflict surrounding management with diagnostic thyroidectomy in the setting of indeterminate FNA results. Methods Patients with indeterminate results of thyroid nodule FNA were prospectively enrolled. All consultations were carried out by three otolaryngologists in a consistent manner. After consultation, participants completed a demographics form and the Decisional Conflict Scale (DCS) questionnaire. Results Thirty-five patients (28 female) between the ages of 30 and 88 years (mean age 54.89) participated. The median total DCS score was 10.94 (interquartile range, 4.69–25.0). Twelve patients (34 %) scored at or above 25 on the DCS, indicating clinically significant level of decisional conflict. Patients reported feeling significantly more confident about their decision after the surgical consultation compared to before the consultation (p = 0.00). The total DCS score was significantly negatively correlated with self-reported confidence after the consultation (r = −0.421, p = 0.012). Conclusion Many patients experienced clinically significant decisional conflict when considering thyroidectomy for management of a thyroid nodule with indeterminate cytopathology. Future research should be directed at developing decision support tools for this patient group, and exploring the impact of decisional conflict on health outcomes.